Integrated hollow fabric structure - CHEN SHIJIE; ZHAO QIAN; MI ZHONG-XING; WANG YOUJIANG (2012)
In one aspect of the invention, an integrated hollow fabric structure includes a body having an axis and a thickness along a direction perpendicular to the axis, at least first and second groups of yarns, the yarns of each group space-regularly disposed in layers, where the yarn layers of the at least two groups of yarns are alternately stacked and interlocked together, and embedded in the body, and a third group of yarns through the thickness of the body to interlock the layers together, where the positions and the pattern of interlocking vary according to the need.